CAVPENET Peptide Inhibits Prostate Cancer Cells Proliferation and Migration through PP1γ-Dependent Inhibition of AKT Signaling - Matos, Bárbara; Gomes, Antoniel A. S. [UNESP]; Bernardino, Raquel; Alves, Marco G.; Howl, John; Jerónimo, Carmen; Fardilha, Margarida (MDPI, 2024)
Protein phosphatase 1 (PP1) complexes have emerged as promising targets for anticancer therapies. The ability of peptides to mimic PP1-docking motifs, and so modulate interactions with regulatory factors, has enabled the creation of highly selective modulators of PP1-dependent cellular processes that promote tumor growth. The major objective of this study was to develop a novel bioactive cell-penetrating peptide (bioportide), which, by mimicking the PP1-binding motif of caveolin-1 (CAV1), would regulate PP1 activity, to hinder prostate cancer (PCa) progression. The designed bioportide, herein designated CAVPENET, and a scrambled homologue, were synthesized using microwave-assisted solid-phase methodologies and evaluated using PCa cell lines. Our findings indicate that CAVPENET successfully entered PCa cells to influence both viability and migration. This tumor suppressor activity of CAVPENET was attributed to inhibition of AKT signaling, a consequence of increased PP1γ activity. This led to the suppression of glycolytic metabolism and alteration in lipid metabolism, collectively representing the primary mechanism responsible for the anticancer properties of CAVPENET. Our results underscore the potential of the designed peptide as a novel therapy for PCa patients, setting the stage for further testing in more advanced models to fully realize its therapeutic promise.
Keywords: PP1-targeting peptide; prostate cancer; protein phosphatase 1; protein-protein interaction; treatment